2022
DOI: 10.1001/jamanetworkopen.2022.24142
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Functional and Structural Neural Network Features in Older Adults With Depression With vs Without Apathy and Association With Response to Escitalopram

Abstract: IMPORTANCEApathy is prevalent among individuals with late-life depression and is associated with poor response to pharmacotherapy, including chronicity and disability. Elucidating brain networks associated with apathy and poor treatment outcomes can inform intervention development. OBJECTIVES To assess the brain network features of apathy among individuals with late-life depression and identify brain network abnormalities associated with poor antidepressant response. DESIGN, SETTING, AND PARTICIPANTS This seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 82 publications
0
11
0
Order By: Relevance
“… 46 While we identified very similar ROIs associated with apathy to previous results on the topic, the directions of the associations we observed were different from those reported in the studies using seed-based approaches. 9 , 47 , 48 These differences might be related to the use of few seeds in previous studies omitting the variability between ROI connectivity within a same RSN. Our findings suggest that the AES might provide a more consistent measure of modified intranetwork connectivity in the DMN in individuals with apathy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 46 While we identified very similar ROIs associated with apathy to previous results on the topic, the directions of the associations we observed were different from those reported in the studies using seed-based approaches. 9 , 47 , 48 These differences might be related to the use of few seeds in previous studies omitting the variability between ROI connectivity within a same RSN. Our findings suggest that the AES might provide a more consistent measure of modified intranetwork connectivity in the DMN in individuals with apathy.…”
Section: Discussionmentioning
confidence: 99%
“… 7 Apathy was also correlated with higher rsFC between the anterior insula and the right DLPFC, mid-cingulate and premotor cortices, and reduced rsFC with the bilateral parietal posterior regions. 8 , 9 This hyperconnectivity between the insula and the DLPFC has been associated with treatment nonresponse in individuals with apathy and LLD, 9 while hypoconnectivity between the dACC and DLPFC has been correlated with poorer executive functions 10 and apathy during effortful emotion recognition 11 in individuals with LLD. Taken together, these results suggest that apathy in LLD and its traits are underpinned by an altered intrinsic rsFC of the executive network as well as a dysconnectivity of the anterior insula to recruit goal-oriented cognitive and motor processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, some studies have found that antidepressant treatments may exacerbate symptoms of apathy 20 . And Lauren et al found in elderly depressed patients that apathy may contribute to antidepressant side effects 21 . In our study, biotypes 1, 2, and 4 have similar symptoms but different or even completely opposite neurobiological bases.…”
Section: Discussionmentioning
confidence: 99%
“… Yuen, et al, [ 139 ] rsfMRI ROI-to-voxel FC right anterior insula, rAI as ROIs AES HC ( n = 10), LLD with apathy ( n = 7) LLD without apathy ( n = 9) LLD with apathy had lower FC within salience network (rAI-dACC) and higher rAI-dlPFC and rAI-PCC FC. Oberlin, et al, [ 140 ] rsfMRI, dMRI ROI-to-Voxel functional connectivity and structrual connectivity AES LLD with apathy ( n = 20) LLD without apathy (n = 20) Among the 40 LLD, 12-week nonrandomized single-group trial of escitalopram, 27 remitted Relative to nonapathetic depression, those depression with apathy had lower FC of SN seeds with the dlPFC, premotor cortex, mid CC, and paracentral lobule and greater FC of SN with the lateral temporal cortex and temporal pole. Compared with depression without apathy, those with apathy had lower structural connectivity in the splenium, cingulum, and fronto-occipital fasciculus.…”
Section: Introductionmentioning
confidence: 99%